2014
DOI: 10.15403/jgld-1275
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal Endoscopy is Preferred by Transoral Endoscopy Experienced Patients

Abstract: Background & Aims: Both unsedated transoral endoscopy (TOE) and sedated TOE have some drawbacks in clinical practice. Unsedated transnasal endoscopy (TNE) has been suggested as an alternative to both methods. This study aimed to determine the advantages of TNE in patients who have previously undergone unsedated conventional TOE.Methods: Patients who had received an unsedated TOE in the last 12 months and were scheduled for a second upper endoscopy were included. They were randomized to undergo either unsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…These advantages imply that TNE is ideal for screening and surveillance programmes (varices or Barrett's) as it is not uncommon for such patients to become increasingly anxious after multiple repeat endoscopies. A recent small randomised trial from Turkey with similar design to our study which included endoscopy‐experienced patients also confirmed that TNE was better tolerated when compared with unsedated standard endoscopy …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These advantages imply that TNE is ideal for screening and surveillance programmes (varices or Barrett's) as it is not uncommon for such patients to become increasingly anxious after multiple repeat endoscopies. A recent small randomised trial from Turkey with similar design to our study which included endoscopy‐experienced patients also confirmed that TNE was better tolerated when compared with unsedated standard endoscopy …”
Section: Discussionsupporting
confidence: 82%
“…Complications reported in other studies included self‐limited epistaxis (0.85–2%), vasovagal events (0.3%), and a single oesophageal perforation . No complications were reported in this study.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Unsedated peroral gastroscopy (ns-oEGD) can increase patients’ discomfort, which may reduce the overall quality of the examination 15 16…”
Section: Introductionmentioning
confidence: 99%
“…In numerous publications, nEGD has been described as a promising alternative, as it reduces cardiac stress level,18 shows good patient tolerance,5 14 16 19–25 leads to less gagging,18 26 and, at the same time, is effective and safe 27 28. Further studies have shown a high rate of completed procedures as well as reselection of nEGD in patients, who experienced the unsedated method before 16 27 29. According to a review on Japanese studies by Tatsumi et al , epistaxis is a main complication in nEGD (0%–5%) 30…”
Section: Introductionmentioning
confidence: 99%